(3JGQjN GdSdWGf Sdje GdYKeGfi eY GdSdWGf bGfUhg GdZhQis - (3CMeO Hf Ydj Hf CMeO Hf RfHd GdQeGd , J HYO (B980 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3hdeG CUHM Gddg HGdUHGM hCVGA HfhQg hdGM QcH GdSdWGf WheGfHGi HYO eGUdi GdUHM s
(3BNQgG (B:s
(3hcGf QGhjgG GdTjN CMeO Hf RfHd QMeg Gddg hEjGfG Bejf s
(3GdLRA GdKGfi jHJOA HPcQ GdSdWGf WheGfHGi hNQhLg Edi GdMQHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B409 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B62 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B44) s
Keywords: (3GdJGQjNs